Digital interventions to moderate physical inactivity and/or nutrition in young people: a Cancer Prevention Europe overview of systematic reviews - McDermott, Kevin T.; Noake, Caro; Wolff, Robert; Bauld, Linda; Espina, Carolina; Foucaud, Jérôme; Steindorf, Karen; Thorat, Mangesh A.; Weijenberg, Matty P.; Schüz, Joachim; Kleijnen, Jos (Frontiers in Digital Health, 2023)
Background Strategies to increase physical activity (PA) and improve nutrition would contribute to health benefits, including reducing cancer risk. The accessibility of digital technologies means they could potentially improve healthy behaviours among young people. Objective We conducted a review of systematic reviews of digital interventions aimed at increasing PA and good nutrition in young people (school-aged children, college/university students, young adults only (over 18 years) and both adolescent and young adults (<25 years)). Methods Searches for systematic reviews were conducted across relevant databases including KSR Evidence (www.ksrevidence.com), Cochrane Database of Systematic Reviews (CDSR) and Database of Abstracts of Reviews of Effects (DARE; CRD). Records were independently screened by two reviewers. Risk of bias (RoB) was assessed with the Risk of Bias Assessment Tool for Systematic Reviews (ROBIS) tool. We employed a narrative analysis. Results 24 reviews were included employing a range of digital interventions. Quality was limited with only one review judged as low RoB. In school-aged children eHealth interventions improved outcomes. Accelerometer-measured (Standardised Mean Difference [SMD] 0.33, 95% Confidence Interval [CI]: 0.05 to 0.61) and self-reported (SMD: 0.14, 95% CI: 0.05 to 0.23) PA increased, as did fruit/vegetable intake (SMD: 0.11, 95% CI: 0.03 to 0.19). No difference was reported for consumption of fat post-intervention (SMD: –0.06, 95% CI: 0.15 to 0.03) or sugar sweetened beverages (SSB) and snack consumption combined post-intervention (SMD: –0.02, 95% CI:–0.10 to 0.06),or at the follow up (SMD :–0.06, 95% CI: –0.15 to 0.03) (low ROB, minimal to substantial heterogeneity). Smartphone based interventions also improved PA (SMD: 0.44, 95% CI: 0.11 to 0.77) when compared to controls, with increases in total PA (weighted mean difference [WMD] 32.35 minutes per day, 95% CI: 10.36 to 54.33) and daily steps (WMD: 1185, 95% CI: 303 to 2068) (high RoB, moderate to substantial heterogeneity). Conclusions We have identified limited evidence that suggests some potential for digital interventions to increase PA and, to lesser extent, improve nutrition in school-aged children. However, effects can be small and based on less robust evidence. There is an urgent need for further research using contemporary technology and appropriate methods.